Non-enzymatic lipid peroxidation from liver, heart and kidney of chinchilla and rat - Gutiérrez, Ana María (2010)
Much work has been carried out on non-enzymatic induced lipid peroxidation from different tissues of rat, but little information is available about this process in chinchilla. Studies were carried out to determine the levels of lipid peroxidation of homogenates isolated from liver, heart and kidney of chinchilla and rat. Fatty acids located in total lipids of tissues studied were determined using gas chromatography and lipid peroxidation was evaluated by chemiluminescence assay. The lipid peroxidation process was more effective in rat liver and kidney homogenates than in chinchilla. In homogenates from liver and kidney of both species a signifi cant decrease of C20:4n6 and C22:6n3 acids were observed during lipoperoxidation. However, changes were not observed in the fatty acid profi les of heart. In the heart fatty acid profi le does not appear to be responsible for the different susceptibility to the lipid peroxidation. These results indicate that a low degree of fatty acid unsaturation in liver and kidney chinchilla, may confer advantage by decreasing their sensitivity to lipid peroxidation process of this specie.